Research methodology in strategy and management. Vol. 3 - Ketchen, David J.; Bergh, Donald D. (Emerald, 2006)
Volume 3 of the Research Methodology in Strategy and Management title offers twelve chapters of discussion surrounding various tools and methods utilized by scholars and academics. A wide range of approaches are covered that will prove to be an important reference and inspiration for strategists, managers, and researchers. It is a resource containing recent research by some of the field's most respected scholars.
Keywords: Business & Economics -- Management.; Social Science -- General.; Business strategy.; Strategic planning.; Management.; elektronické knihy; electronic books